Analysis of interleukin-10 gene polymorphisms in patients with chronic periodontitis and healthy controls - Moudi, Bita (Dent Res J (Isfahan), 2018)
BACKGROUND: Interleukin-10 (IL-10) is an anti-inflammatory cytokine that has important roles in the periodontal diseases. The IL10-1082, -819, and -592 polymorphisms in the promoter region of IL-10 gene have been associated with various IL-10 expressions. The aim of this study was to investigate the association between these gene polymorphisms with chronic periodontitis in a sample of Iranian populations from Southeast of Iran. MATERIALS AND METHODS: IL-10 single nucleotide polymorphisms were analyzed in 210 patients with chronic periodontitis (CP) and 100 individuals without CP by polymerase chain reaction-restriction fragment length polymorphism method. Statistical analysis of data was performed using the Chi-square test. The risk associated with single alleles, genotypes, and haplotypes were calculated by performing a multiple logistic regression analysis to estimate the odds ratio (OR) and 95% confidence interval (CI). P < 0.05 for statistical significance. RESULTS: The prevalences of AG and GG genotypes of IL10-1082 were significantly different between CP and control groups in comparison to AA genotype (OR = 2.671; CI = 1.482–4.815; P = 0.001 for AG vs. AA, OR = 4.151; CI = 2.128–8.097; P < 0.001 for GG vs. AA). In addition, subjects with at least one IL10-1082-G allele were significantly had an increased risk for CP (OR = 2.157; CI = 1.531–3.038; P < 0.001). The distribution of the IL10-819 and IL10-592 genotypes was not different between CP and control subjects (P = 0.109 and P = 0.139, respectively). The combination of different genotypes showed that GCC haplotype was significantly different between groups (OR = 4.379; CI = 1.077–17.807; P = 0.039). CONCLUSION: The results demonstrated that IL10-1082 polymorphism was a putative risk factor for chronic periodontitis and associated with increased susceptibility to CP.